(3OjhGf CHj fhGSs - (3CHh fhGS , GdMSf Hf gGfjA Hf YHO GdGhd Hf UHGM GdMcej HGdhdGA, CHh fhGS,J (B198 (3g` s ((3CHhHcQ Hf Ndjd Hf eMeO GdedWjhj s)
(3ChdgG (B:s
(3CSbjfgG HShGO bHd JZQjO GdefGOj s
(3BNQgG (B:s
(3hjdj Ydi fLd GdYjhf dh Cfge YGLhG Ydj aSdehG Ch YQLhG hgPG BNQ OjhGf CHj fhGS QMeg Gddg s
(3fSNI KGdKIs
(3hgj UfYI MeRI GdCUagGfjs
(3hjdGMX Cf GdJUhjQ Ydi UaMI hGMOI hGdUaMI GdebGHdI dgG aGQZIs
(3hQO CjVkG JMJ Qbe (B475(3, (B2181(3, (B2191 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B240s
Keywords: (3GdCOHs